Pengaruh Pembelajaran Kooperatif tipe STAD terhadap Hasil Belajar Matematika Ditinjau dari Motivasi Belajar - Maya Nurfitriyanti; Witri Lestari (Universitas Indraprasta PGRI, 2015)
The aim of the research: 1) the effect of learning method on mathematics achievement, 2) the effect of learning motivation on mathematics achievement, 3) interaction of learning method and learning motivation on mathematics achievement. It is quantitative research with experimental research. This research compared two classes with two different methods. The first class is an experiment class which was thought by cooperative learning method type STAD, whereas the second class is control class which was though by conventional learning method. This research was conducted in Taruna Bhakti Vocational High School, the amount of sample is 64 learners. Statistic was used in this research was two way ANOVA and continued with tukei test. The result of this research: 1) students’ mathematics achievement with cooperative learning method is greater than conventional method, 2) students’ mathematics achievement with high motivation is greater than less motivation, 3) there was interaction between learning method and motivation on mathematics achievement.